Analysis of the Comparative Study on Flower Pigments with Phenylalanine Ammonia-Lyase Activity in Orchid Plants - Suat Hian Tan; Nyuk Ling Ma; Wan Nurul Hidayah Wan Anuar (Challenging Issues on Environment and Earth Science Vol. 3, 2021)
Background: Orchidaceae plants have been one of the most important industrial products in the agricultural industry around the world. Since the flower petals have eye-catching pigments, they can be used as cut flowers in addition to being potted flowers. Objective: The key pigments found in orchid flower petals were studied, as well as their relationships to phenylalanine ammonia-lyase (PAL) activity. Results: Total anthocyanin content of six different orchids’ petals was determined specthrophotometrically and the value ranged from 0 mg/g (in Dendrobium Shavin white) to 2.128 mg/g (in Mokara Aranda). The petals with vivid colour have a high amount of anthocyanin content, while, they have a high amount of chlorophyll content for those with pale colour. Total anthocyanin content was found to be the highest when compare to ?-carotene and chlorophyll content. PAL behaviour was found to be significantly positive associated with anthocyanin content in correlation analysis. Conclusion: The results indicate the potential for PAL enzyme as a biomarker for flower colour in orchids.